Lesões decorrentes de obstruções experimentais no jejuno de eqüinostratados com glutamina ou associação de succinato sódico dehidrocortisona, dimetilsulfóxido, pentoxifilinae ácido ascórbico - Geane Maciel Pagliosa (2009)
Under general anesthesia and arterial pressure control, eighteen horses were submitted simultaneously todistension and complete venous ischemia of jejune for two hours, followed by twelve hours ofreperfusion. Six horses (T1 group) were treated with intravenous 2% glutamine (50mg/Kg), six horses(T2 group) were treated with an association of hydrocortisone succinate (4mg/Kg), pentoxifylline(8mg/Kg), ascorbic acid (50mg/Kg) and dimetylsulfoxide (20mg/Kg), and six horses (group C) weretreated with ringer lactate solution in same volume. The treatments were performed at 1h after thebeginning of ischemia and glutamine was also administred at 6h after reperfusion, when the other groupsreceived ringer lacatate solution. Intestinal samples were collected before the onset of ischemia and at 2hof ischemia and, in at 2 and 12h of reperfusion for histopatological analyses, ultrastructural examination,measurement of area and number of villus per mm2, myeloperoxidases activity and tumor necrosis factoralpha (TNF-s) and granulocytes chimiotaxic protein 2 (GCP-2) expression analysis. After 12h ofreperfusion samples of lungs, kidney, spleen, heart, pancreas, liver and lamellar corium tissue were alsocollected for histopatological and MPO evaluation. There were no statistical differences between groups,therefore, along the time in groups T1 and T2 in venous ischemia segment, the mucosal erosion at 12 ofreperfusion and hemorrhage at 2h of reperfusion were statistical lower. It was concluded that thetreatments attenuated the mucosal erosion and hemorrhage caused by ischemia and reperfusion in jejuneunder complete venous obstruction in equine